Intraventricular Squamous Papillary Craniopharygioma. - Madhavan, Manoharan; P., Jain George; J., Abdullah Jafri; Idris, Zamzuri (International Academy of Cytology, 2005)
Squamous papillary craniopharyngioma is a distinct entity, and its cytologic features may be misleading. Because of the rarity of this tumor,this case is being reported. with a note on the cytologic features.